Training and competition injury epidemiology in professional basketball players: a prospective observational study - Moreno-Pérez, V.; Ruiz, J.; Vazquez-Guerrero, J.; Rodas, G.; Del Coso, J. (The Physician and Sportsmedicine, 2023)
Background There is a lack of epidemiological data comparing the characteristics of injuries sustained during basketball matches vs. training taking into account incidence, type of injury, body location and risk factors associated with the development of the injury.